Internet-of-Things (IoT)-Based Smart Agriculture and Precision Irrigation for Agriculture- an Intelligent Water Management - Kumar Sharma, Vineet; Jeberson, Wilson; Kumar Isaac, Rajendra (Yugoslav Journal of Operations Research; Online firstDO - 10.2298/YJOR240315014S, 2025)
The agricultural industry is experiencing a transformative shift through the adoption of Internet-of-Things (IoT) technology, often termed as "smart agriculture." This paradigm shift is revolutionizing traditional farming practices, making them more precise, efficient, and data-driven. This study presents a novel contribution to the field by developing an intelligent water management system using IoT sensors, specifically designed for precision irrigation. Unlike existing systems, this solution enables real-time monitoring of critical environmental parameters such as soil moisture, humidity, and temperature with unparalleled accuracy. The unique contribution of this work lies in its data-driven approach to optimizing irrigation practices, which not only enhances water-use efficiency but also significantly improves crop yield and quality. Furthermore, the system's capability for remote monitoring and management minimizes the need for manual interventions, thereby reducing operational costs. The study demonstrates the practical application of IoT in mitigating water management issues and increasing agricultural productivity, particularly in the context of climate change challenges. This work provides a scalable and sustainable model for IoT adoption in agriculture, offering a robust framework for improving efficiency, sustainability, and resilience in farming practices.